The Effect Of Soaking Vitamin C On Egg Hatchability, Growth And Survival Of Larvae (Colossoma macropomum) - Wewi Lorenza; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT         This study was conducted on December 2019 –February2020 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, University of Riau, Pekanbaru. The purpose of this study was to determine the effect of vitamin C on hatchability of eggs, growth, and survival oflarvae. This study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications. The dose of vitamin C solution used isC0 (0 mg/L), C50 (50 mg/L), C100 (100 mg/L), C150 (150 mg/L) and C200 (200 mg/ L). Immersion of Freshwater Pomfret eggs with vitamin C for 3 hours with density 150 eggs and water volume 1 L. Larvaewere maintained for 20 days. The results showed that different dose of vitamin C solution had a significant effect (P <0.05) on fertilization rate (88.66%), hatching rate (91.33%), and absolute length growth (1.26 cm). However, it did not have a significant effect (P> 0.05) on absolute weight growth, specific growth rate and survival rate of larvae. The best dose of vitamin C to increase the fertilization rate, hatching rate and absolute length growth was 150 mg/L. The water quality during the study was temperature26.3-28.2 ºC, pH water 5.5-5.8, pH of hatching water 5.9-6.3, pH of larvae maintenance water 5.7-6.5 and DO 6.0-6.6 mg/L.Keywords :  Colossoma macropomum, Vitamin C,  Fertilization Rate,Hatching Rate,Growth, Survival Rate